2019
DOI: 10.1590/1517-869220192506149743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Different Methods for Measuring Body Fat After a Weight Loss Program

Abstract: Introduction: Accurate and sensitive measurement of body composition is an important tool in the diagnosis and control of obesity. Objective: To compare body fat changes measured by dual-energy X-ray absorptiometry (DXA), bioelectrical impedance analysis (BIA), and skinfolds (SK) in healthy overweight adults in order to evaluate whether all three methods can be used during a weight loss program (WLP). Methods: Eighty-four men (n=36) and women (n=48), body mass index 25-29.9 kg/m 2 , aged between 18-50 years, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…In the review, the mean age of the participants, existing diseases, and the status of general obesity also had a significant effect on waist circumference reduction [33]. Despite important elements found in previous studies (self-monitoring [8,61], in-person feedback [34], targeted and structured lifestyle coaching [34,61], program use [61], and social support [61]), only personal feedback and the quality of the studies were related to greater changes in body composition in our findings. Khaylis et al [97] qualitatively studied components that are effective in facilitating weight loss.…”
Section: Principal Findingscontrasting
confidence: 43%
See 1 more Smart Citation
“…In the review, the mean age of the participants, existing diseases, and the status of general obesity also had a significant effect on waist circumference reduction [33]. Despite important elements found in previous studies (self-monitoring [8,61], in-person feedback [34], targeted and structured lifestyle coaching [34,61], program use [61], and social support [61]), only personal feedback and the quality of the studies were related to greater changes in body composition in our findings. Khaylis et al [97] qualitatively studied components that are effective in facilitating weight loss.…”
Section: Principal Findingscontrasting
confidence: 43%
“…Bioimpedance measures the electrical properties of body tissues as alternating electric current flows through a human body using parameters such as fat-free mass or total body water [7]. Another example is DXA, which is a 3-component model (1 component of fat mass and 2 components of fat-free mass), but it is not widely used because of its high cost and risk of unnecessary radiation exposure for patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, differences in the accuracy of the values obtained in the comparison between DXA and BIA using different BIA machines has also been reported [80]. Finally, differences between the results obtained from the skinfold prediction equations compared to DXA have been shown in the literature [81,82]. Some other limitations should be mentioned, including the use of cross-sectional data (or collected by us cross-sectionally from longitudinal studies for needs related to the statistical processing of data), since this type of study design makes it difficult to explore causalities.…”
Section: Strength and Limitationsmentioning
confidence: 98%
“…Ferrari et al [73] found that self-reported measures significantly underestimated sedentary time and overestimated PA time compared using different BIA machines has also been reported [80]. Finally, differences between the results obtained from the skinfold prediction equations compared to DXA have been shown in the literature [81,82].…”
Section: Association Between Pa and Body Composition Parametersmentioning
confidence: 92%